2015
DOI: 10.1371/journal.pone.0128388
|View full text |Cite
|
Sign up to set email alerts
|

“Let Me Hear Your Handwriting!” Evaluating the Movement Fluency from Its Sonification

Abstract: The quality of handwriting is evaluated from the visual inspection of its legibility and not from the movement that generates the trace. Although handwriting is achieved in silence, adding sounds to handwriting movement might help towards its perception, provided that these sounds are meaningful. This study evaluated the ability to judge handwriting quality from the auditory perception of the underlying sonified movement, without seeing the written trace. In a first experiment, samples of a word written by chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…linking the properties of drawing movements to their evocation through timbre variations of friction sounds. Studies by Danna et al [ 33 ] confirmed such binding between friction sounds and drawing movements by showing that the quality of handwriting can be accurately judged through friction sounds evoking the movement velocity. Such unified percepts that link sounds and actions have also been shown for footstep sounds [ 34 ].…”
Section: Discussionmentioning
confidence: 93%
“…linking the properties of drawing movements to their evocation through timbre variations of friction sounds. Studies by Danna et al [ 33 ] confirmed such binding between friction sounds and drawing movements by showing that the quality of handwriting can be accurately judged through friction sounds evoking the movement velocity. Such unified percepts that link sounds and actions have also been shown for footstep sounds [ 34 ].…”
Section: Discussionmentioning
confidence: 93%
“…The sound model used for sonification was created using the SuperCollider 7 programming language. The model exploited harmonic pitch sensitivity, physical interpretation of spectral slope and amplitude, as well as a noise generator that could move from coarse, gravel-like sounds, to smoother sounds reminiscent of a water stream or wind.…”
Section: Methods Of Experimentsmentioning
confidence: 99%
“…-Slider 2: The amount of high frequency content in the noise source. 7 http://supercollider.github.io/.…”
Section: Methods Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…When associated with a biological law, a specific calibration of the velocity profile enables the evocation of a human gesture (Thoret et al 2014). Such a synthesis tool has been used in several applications, for instance for video games (Pruvost et al 2015) and associated with a graphic tablet to sonify handwriting as a remediation device for dysgraphic children (Danna et al 2015).…”
Section: Perception Of Various Actionsmentioning
confidence: 99%